LEMBAGA PENDIDIKAN MASYARAKAT SERTA TANGGUNG JAWAB PEMERINTAH TERHADAP MASYARAKAT - Sari Kurniah Simamora; Wahyuni Yuni Pandiagan; Ilham Ilham Satriawan; M. Irham Maskuri Sitompul (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2021)
Abstract: Educational institutions are a useful forum for fostering human beings, leading to a better future. Everyone who is in the container will experience changes and developments according to the color and style of the institution. In educational institutions, society is the third environment after family and school. Community is defined as a group of people who occupy an area, are bound by the same experiences, have a number of adjustments and are aware of their unity, and can act together to meet their life crises. the course of the educational institution. The central and regional governments are the embodiment of the nation's community and the state. The government carries the public trust to manage all aspects of the nation's life (in the field of education). These responsibilities include: 1. State and community responsibilities in the form of motivation to preserve the upholding of the independence of the nation and state. This responsibility includes fostering national awareness, having a national ideology and having a constitution. 2. Responsibilities of structural institutions, namely as a form of state institutional arrangements with each aspect of their responsibilities. Can also be interpreted as a juridical-constitutional responsibility.Keyword : Community Education Institutions, Government Responsibility